Sapo y Sepo, un año entero - Lobel, Arnold ([Madrid] : Alfaguara, 1988)
Two friends share experiences in each season of the year.
Translation of: Frog and toad all year.
K-3
Text in Spanish.
K-3
Notable/Best Books (A.L.A.)
School Library Media Quarterly (A.A.A.L.)
Keywords: Friendship -- Fiction; Frogs -- Fiction; Spanish language materials; Toads -- Fiction; Friendship -- Fiction; Frogs -- Fiction; Spanish language; Toads -- Fiction